Mengenal Banten Prayascitta Sebagai Penyeimbang Perilaku Di Bhuwana Agung Dan Bhuwana Alit Untuk Penjatuhan Sanksi Adat Di Bali - Setiawan, I.G Ngurah Oka Putra (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
Belief in religion and tradition is contained in one meaning, namely Tri Hita Karana, which is believed by the Balinese Hindu community. This concept teaches that the ancestors of Balinese Hindus emphasized the importance of relationships and interconnectedness in life in the world. This relationship must be maintained so that the ecosystem, which is termed Bhuwana Agung and Bhuwana Alit, remains balanced, both in Niskala and Skala, avoiding the impact of individual behavior in community groups. This study employs a normative juridical method with a qualitative approach that is sui-generis, combining empirical analysis with normative legal studies of the applicable law. Based on the relationship between Balinese traditions and Hindu teachings, it can be concluded that Balinese Hindus are taught to uphold attitudes and daily actions to maintain balance between Bhuwana Agung and Bhuwana Alit. If this is ignored, then the banten prayascitta will function to balance the relationship, as a way to atone for the mistakes that have been made so that nature remains in a state of balance.